Adverse associations of infant and child sleep problems and parent Health: An Australian population study - Hiscock, H; Wake, M; Davy, B; Martin, J; Hardy, P (My University, 2007)
This paper examined the relationships between child sleep problems and maternal and paternal mental health and general well-being. Data from wave 1 of the Longitudinal Study of Australian Children was used, incorporating both the infant and preschool-aged cohorts. Moderate to severe sleep problems affected 17% of infants and 14% of preschool-aged children, and prevalence of severe psychological distress in parents ranged from 3% to 5%, and prevalence of poor general health in parents ranged from 8% to 11%. The analysis found that sleep problems in infants were associated with poor general health in either parent and that preschool sleep problems were associated with poor general health in mothers.
Pediatrics
Keywords: Child Development -- Sleep; Child Development; Childhood and child development; Child Development; Sleep; Childhood and child development